Analisis Penggunaan Media Digital Interaktif Untuk Meningkatkan Hasil Belajar Siswa Dalam Pembelajaran Matematika DI Sekolah Dasar - Ronalita Simorangkir; Rina Sinaga; Romasda Limbong; Zaira Nazwa (Trapsila: Jurnal Pendidikan Dasar, 2023)
The very rapid development of technology has various positive impacts on human life, especially in the field of education. The aim of this research is: This research aims to explain the use of interactive learning media which can influence the learning outcomes of elementary school students. This research is qualitative research in the nature of a library study by examining trusted sources either in written form or in relevant digital format without going directly to the field. Based on a literature review analysis of several scientific articles, it was found that the use of digital learning media can improve the learning outcomes of elementary school students.Keywords: digital media, elementary school